Effect Of Different Extraction Solvents on Antioxidant Properties of Water Lily (Nymphaeceae Antares) Flower Petal And Stamen. - Hafiza Yahya; Mohd Zin, Z; Sanuri, A.Z.M.; Bashah, N.; Ibrahim, K.; Zainol M.K. (Rynnye Lyan Resources, 2024)
Indexed by SCOPUS/MYCITE